Numerical Symbolism in the Musical Dramaturgy of The Queen of Spades by Pyotr Tchaikovsky - Vladimir V. Goryachikh (Современные проблемы музыкознания, 2025)
Hermann’s obsession with the three, seven and ace of cards, which “never left his head and moved on his lips,” “haunting him in his sleep, taking on all possible forms,” is one of the most striking and memorable artistic discoveries in Pushkin’s story. Perhaps it was this idea, successfully picked up by Modest Ilyich Tchaikovsky and developed in the original version of the libretto, that so inspired his brother, the composer Pyotr Ilyich Tchaikovsky, with the plot of The Queen of Spades. The individual observations accumulated over the past years on the reflection of number symbolism in the literary and musical language of The Queen of Spades pose the question to the researcher: to what extent was the unfolding of this process in the composer’s consciousness rational. It is precisely the totality of the manifestations of this plan, its action in musical dramaturgy at the level of rhythm (rhythmic patterns and figures that form groups of three, seven and twelve durations), metre (the most indicative is the choice of the rare time signature 12/8 and giving it leitmotiv status in the part of the Countess), harmony (three-chord chains), mode (the use of whole-tones not only brings in a rich colouring, but also becomes one of the “building blocks”), tonal plan (h/H as the most important tonal centre), musical syntax (“tripleness” in the organization of motives and phrases), melody and — more broadly — thematics, as well as composition convinces us that before us lies a complete system that has been reproduced probably for the first time in world opera literature. Keywords: The Queen of Spades, opera, Pyotr Ilyich Tchaikovsky, Modest Ilyich Tchaikovsky, Alexandr Pushkin, number symbolism, musical dramaturgy, composition, libretto For citation: Goryachikh, V. V. (2025). Numerical Symbolism in the Musical Dramaturgy of The Queen of Spades by Pyotr Tchaikovsky. Contemporary Musicology, 9(2), 106―133. https://doi.org/10.56620/2587-9731-2025-2-106-133